Kualitas Briket Arang Serbuk Limbah Bangkirai, Rengas dan Agathis: Charcoal Briquette Quality of Bangkirai, Rengas and Agathis Waste Powders - Alpian, Alpian; Sianipar, Defi; Koroh, Desy Natalia; Yanciluk, Yanciluk; Nuwa, Nuwa; Supriyati, Wahyu; Surasana, I Nyoman; Luhan, Gimson; Wanasetya, Ayub (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2023)
Central Kalimantan has many types of wood such as Rengas (gluta sp), Bangkirai (shorea laevifolia endert), and Agathis (agathis spp). The third type of woods are found in the company of furniture as a result of waste in powder form so that it can be utilized for the manufacture of charcoal briquettes. The purpose of the research is to find out the characteristics of charcoal briquettes from wood waste Rengas, Bangkirai, and Agathis which refers to the Indonesian National Standard (SNI 01-6235-2000). The treatment of this research done on Bangkirai wood, Rengas, and Agathis which have different density with 5 replications so that the samples obtained 15 pieces. Data analysis was conducted to determine the effect of the treatment on the character of the studied and if it has significant effect then it is analyzed test difference average middle value that is specified by Coefficient Value of Diversity. Charcoal briquettes testing generally meets Indonesian National Standard (01-6235-2000) on charcoal briquettes except for volatile substances. The research data finding from these three types of wood which examined showed that the type of Bangkirai wood powder has the best charcoal briquette quality because of lower water content is at 5.05%, the higher density is 0.72 g/cm3, the ash content is 1.9% , carbon bound is 63.30%, volatile substance content is 29.75%, press firmness is 41.67kg/cm2, and calorific value is 6958.94 kal/g